Performance of a free standing air-cooled condensing unit in a confined space in hot and humid climates / Amar Sidik - Sidik, Amar (2015)
The purpose of the research is to analyze the performance of free standing air-cooled condensing unit in a confined space under hot and humid environment. The performance is measured based on the on coil temperature, which determines the capability of air cooled condenser to operate under limited air circulation as this will affect the final outcome of performance of the evaporator unit (cooling coil). The work was initially carried out based on a single condenser unit and using the validated computational fluid dynamic (CFD) model to investigate a multi-storey building. From the result, the size ofa confined space of2m X 3.3m X 1m for 6 storey building with 4 meters protruding wall is sufficient to maintain the on-coil temperature within 10°C against the ambient temperature of33.5°C. The outcome of the research can be used as a guide for designing a space for condenser to be installed outside the building.